2020
DOI: 10.1002/joc.6440
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the modified mosaic approach method on regional simulations of surface meteorological variables in western China

Abstract: In this article, a modified mosaic approach method (MMAM), which considers the subgrid‐scale effect of topographical height on atmospheric forcing, is introduced. Two experiments are designed to study the effects of MMAM on surface meteorological variables in Western China within the weather research and forecasting (WRF) modelling framework during June to August 2010. Results show that MMAM has obvious effects on surface 2 m temperature improvement. Simulations of the surface 2 m temperature with MMAM are clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…Previous research results show that the improvement of surface heat flux based on RCMs is helpful to the improvement of the temperature and precipitation prediction (Chen et al, 2019;Li et al, 2016). Li et al (2016) found that the intensity of simulated sensible heat flux over Asian continent in regional models can induce tropospheric temperature anomaly over land.…”
Section: Planetary Boundary Layer Ysumentioning
confidence: 99%
“…Previous research results show that the improvement of surface heat flux based on RCMs is helpful to the improvement of the temperature and precipitation prediction (Chen et al, 2019;Li et al, 2016). Li et al (2016) found that the intensity of simulated sensible heat flux over Asian continent in regional models can induce tropospheric temperature anomaly over land.…”
Section: Planetary Boundary Layer Ysumentioning
confidence: 99%
“…Assuming homogeneity of these processes within LSM grid cells neglects the nonlinear nature of the system; which can ultimately lead to various estimation issues (e.g., errors in estimation for development of the planetary boundary layer, initiation of shallow and deep convection, and cloud formation and precipitation) (Fisher & Koven, 2020; Simon et al., 2021; Tesfa et al., 2014; Vergopolan et al., 2022). Hence, correctly representing the effects of this physical heterogeneity in the LSM macroscale grid cells is vital to accurately represent weather and climate dynamics, as well as the hydrologic cycle (Chen et al., 2020; Li et al., 2013; Salmun and Molod, 2006).…”
Section: Introductionmentioning
confidence: 99%